The role of the skin microbiome in the development of acne and inflammatory dermatoses - Naguliak, Halyna (Global Prosperity, 2025)
Abstract. The article reviews current ideas about the role of the skin microbiome in the occurrence and progression of acne and inflammatory dermatoses. It is emphasized that the skin microbiome is a complex ecosystem that is in close interaction with the immune system and barrier structures of the epidermis. An imbalance of microbial communities causes the development of chronic inflammation, enhances hyperkeratinization processes, increases sensitivity to opportunistic microorganisms and contributes to the formation of clinical manifestations of acne and dermatoses. The paper presents a diagnostic and therapeutic algorithm for assessing the state of the microbiome, which includes a phased selection of biological material, laboratory testing (microbiological and molecular methods) and interpretation of the results taking into account clinical symptoms and concomitant pathology. The importance of microbiome analysis as a tool for personalized therapy selection is revealed, which allows to increase the effectiveness of treatment, reduce the risks of antibiotic resistance and shorten the terms of remission. Particular attention is paid to methods of microbiome modulation: the use of probiotics, prebiotics, symbiotics, topical preparations based on bacterial lysates and modern anti-inflammatory drugs. Clinical cases are presented that confirm the effectiveness of using a comprehensive approach involving microbiome correction in treatment regimens for acne and inflammatory dermatoses. The results obtained demonstrate the prospects for integrating microbiome technologies into the practice of dermatology, since this contributes not only to treatment, but also to the prevention of relapses, the restoration of skin barrier functions and the improvement of patients' quality of life.